Fabrication of glucose-loaded lipid-polymer hybrid nanoparticles for antibacterial applications - Ser, Tammy Ai Li (Nanyang Technological University, 2021)
Antibiotic resistance was reported to be one of the major health challenges which resulted in more than 35,000 deaths. At least 2.8 million people are affected by antibiotic-resistant infections in the U.S. each year. One of the main causes of antibiotic resistance is the formation of biofilm in the body. Biofilm creates a barrier that prevents penetration of the infected area hence antibiotic is not able to reach and kill the bacteria in the infected area. Lipid coated nanoparticle with a polymer core is a potential solution to cure this problem as nanoparticles can penetrate the biofilm matrix easily. The lipids coated on the nanoparticle can protect the encapsulated drugs from binding with the matrix material and enzymatic inactivation in the infection site. The main focus of this project is to study how lipid-coated nanoparticles interact with the biofilm matrix. Also, how adding metabolites such as glucose will potentiate the antibiotic to increase the uptake of it. The lipids used in this study will be DOTAP and DSPC with a polymeric core of PLGA, glucose will be encapsulated as well. Lipid-coated nanoparticles will be fabricated through fluidic fabrication, their particle size will be characterized using Dynamic Light Scattering (DLS). Zeta potential will be tested to know the surface charge of the nanoparticles. A glucose test was done to identify if glucose was encapsulated successfully, loading efficiency and encapsulation efficiency will be calculated for successful encapsulation. Through the Pareto plot plotted, our finding shows that the interaction of DOTAP: DSPC concentration in PVA and PLGA concentration is significant for particle size, zeta potential, and loading efficiency. We calculated the loading efficiency and encapsulation efficiency of the glucose. Results have shown that samples 1 to 4 and 13 showed no glucose encapsulation. While Sample 5 has the most loading followed by Sample 6. Sample 5 and 6. Samples that have a higher percentage of encapsulation efficiency has larger particle size and lower zeta potential as the larger particle size can encapsulate more glucose.